Biological studies on exogenous NO stress to improve the quality of Radix Scutellariae herbs - Kai Zhao; Yafei You; Jincai Lu; Ling Cao; Xiangcai Meng (PLoS ONE, 2025)
Radix Scutellariae, a crucial botanical drug widely used in Asian countries, is derived from the roots of Scutellaria baicalensis Georgi and exhibits diverse pharmacological activities, including antipyretic, analgesic, anti-inflammatory, antibacterial, antiviral, sedative, hypotensive, hypolipidemic, hepatoprotective, and choleretic effects. Owing to excessive market demand, the wild resources are insufficient, and cultivated Radix Scutellariae has thus become the primary source; however, this shift has resulted in a decline in medicinal quality. To address this quality issue, the present study proposes the hypothesis that exogenous nitric oxide (NO) enhances secondary metabolism in fresh roots of S. baicalensis Georgi via reactive oxygen species (ROS)-mediated pathways, thereby improving its medicinal quality. Fresh roots of S. baicalensis Georgi were treated with sodium nitroprusside (SNP) at concentrations of 0.0, 7.5, and 20 mmol/L to induce ROS bursts. At the optimal concentration of 20 mmol/L SNP, the levels of superoxide anion radicals (O 2 ·⁻), hydrogen peroxide (H 2 O 2 ), and malondialdehyde (MDA) increased by 95.1%, 134.5%, and 211.5%, respectively ( P < 0.01). Correspondingly, the activities of antioxidant enzymes—including superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD)—rose by 87.2%, 47.5%, and 59.4%, respectively ( P < 0.01). The activity of phenylalanine ammonia-lyase (PAL), a key enzyme in flavonoid biosynthesis, increased by 70% ( P < 0.01). While the contents of major secondary metabolites (baicalin and wogonoside) remained stable, the levels of their high-activity derivatives (baicalein and wogonin) increased dramatically by 1603.2% and 1256.1%, respectively ( P < 0.01). Pharmacological assays revealed that 20 mmol/L SNP treatment enhanced pharmacological activities: the inhibition rate of body temperature elevation in rats, the inhibition rate of writhing response in mice, and the inhibition rate of auricular swelling in mice increased by 11.7%, 14.9%, and 27.4% ( P < 0.01), respectively. This treatment also reduced serum interleukin-6 (IL-6) and tumor necrosis factor- α (TNF- α ) levels in mice by 13.5% and 16.8% ( P < 0.01), respectively. Collectively, this study confirms that exogenous NO induces ROS bursts in fresh S. baicalensis Georgi roots and improves the quality of cultivated Radix Scutellariae via ROS-mediated enhancement of secondary metabolism, and clarifies the NO-ROS-secondary metabolism regulatory axis, providing valuable insights for quality improvement strategies of other medicinal plants.